IMPLEMENTATION OF INCLUSIVE EDUCATION CURRICULUM IN SECONDARY SCHOOLS - Alfarisi, Muhammad Salman; Faiz, M (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Inclusive education is an educational approach that aims to provide equal learning opportunities for all students, including students with special needs. This article aims to analyze the implementation of inclusive education curricula in secondary schools, focusing on challenges, implementation strategies, and outcomes achieved. This study uses qualitative methods with data collection techniques through interviews and observations in several secondary schools. The study's results indicate that despite various challenges, implementing an inclusive curriculum can improve the engagement and academic achievement of students with special needs.